Clinical and microscopic features of generalized discoid lupus erythematosus in dogs (10 cases). Issue 6 (16th October 2016) - Banovic, Frane; Linder, Keith E.; Uri, Maarja; Rossi, Michael A.; Olivry, Thierry
Abstract : Background: Generalized discoid lupus erythematosus (GDLE) is a newly recognized canine variant of chronic cutaneous lupus erythematosus (CLE) that is not well characterized. Hypothesis/Objectives: We report herein the signalment, clinical signs, treatment outcome, histopathology and immunological findings of 10 dogs with GDLE. Methods: Inclusion criteria were: (i) a >3 month history of generalized skin lesions indicating a chronic or recurrent nature; (ii) skin lesions resembling those of human GDLE; (iii) histopathology of CLE (lymphocyte‐rich interface dermatitis). Direct immunofluorescence (IF) and antinuclear antibody serology were investigated whenever possible. Results: Various breeds were affected in their mid‐ to late adulthood. Selection criteria of generalized multifocal, annular ("discoid") to polycyclic plaques with pigment changes, erythematous margin, adherent scaling, follicular plugging and central alopecia were shown in all dogs. In nine dogs, plaques contained mild to moderate central scarring with depigmentation and/or hyperpigmentation. There were no dogs in which the disease progressed to systemic lupus erythematosus within a median follow‐up of 2.5 years. Per inclusion criteria, interface dermatitis occurred with basement membrane zone (BMZ) thickening, suprabasal apoptosis and/or dermal fibrosis in some dogs. Infundibular interface folliculitis was common; it sometimes transitioned to mural folliculitis in lower follicle segments, and occurred with follicular and sebaceous gland atrophy. The direct IF revealed patchy deposition of immunoglobulin IgG and IgM at the BMZ. Lesions responded to a variety of treatments, including ciclosporin, hydroxychloroquine, topical tacrolimus and tetracycline/niacinamide. Relapses were common after medications were tapered. Conclusions and clinical importance: These observations support the existence of a canine homologue of human GDLE. Abstract : Background – Generalized discoid lupus erythematosus (GDLE) is a newly recognized canine variant of chronic cutaneous lupus erythematosus (CLE) that is not well characterized.Hypothesis/Objectives – We report herein the signalment, clinical signs, treatment outcome, histopathology and immunological findings of 10 dogs with GDLE.Conclusions and clinical importance – These observations support the existence of a canine homologue of human GDLE.